The effectiveness of home-based nursing intervention in the elderly with recurrent diabetic foot ulcers: A case report - Annisa Wuri Kartika; Widyatuti Widyatuti; Etty Rekawati (SAGE Publishing, 2021)
Background: Inadequate glycemic control usually leads to peripheral neuropathy, vasculopathy, and foot deformities that leads to diabetic foot ulcer (DFU), and a 10-years history of diabetes and inadequate self-management increases the risk of reoccurring DFU. A home-based intervention program, which includes Diabetes Self-Management Education (DSME) and wound care is the most likely approach, to engage families and overcoming the barriers in self-care management. The aim of this study is to provide an overview on the effectiveness of home-based nursing intervention in the elderly patients with reoccurring diabetic foot ulcers. Design and method: In this study, a case study approach was used that presented a case related to self-management and wound care in elderly patients with reoccurring DFU. The intervention was carried out by the community health nurses for eight weeks with home visit. Results: Significant changes were reported in diabetes self-management practices, blood glucose level, and wound healing. The Diabetes Self-Management Questionnaire (DSMQ) score increased from 5,62 to 8,54 and the Summary of Diabetes Self-Care Activities (SDSCA) score increased from 3,2 to 6. The Bates Jansen Examination score decreased from 24 and 26 to 17 and 14 in six weeks. Conclusions: The results confirm that family-based interventions program are effective in improving glycemic control and wound healing. Community nursing is believed to prevent an increase in self-management behavior to prevent recurring DFU and maintain a healthy life-style about diabetes self-management education.